The Effect of PhET Chemistry Simulations and Learning Motivation ‎on Senior High School Students’ Chemistry Conceptual ‎Understanding of Molecular Shape - Vinenda Paramita Sirait; Jasrial; Abna Hidayati; Mutiara Felicita Amsal (ISEJ : Indonesian Science Education Journal, 2026)
This study aimed to analyze the effect of PhET Chemistry Simulations and learning motivation on senior high school students’ understanding of molecular shape concepts. The study employed a quasi-experimental method with a 2 × 2 factorial design involving 60 tenth-grade students divided into an experimental class using PhET Chemistry Simulations and a control class receiving conventional instruction. Data were collected through a chemistry conceptual understanding test and a learning motivation questionnaire and analyzed using descriptive statistics and Two-Way ANOVA at a significance level of 0.05. The results showed that students taught using PhET Chemistry Simulations achieved higher conceptual understanding than those taught conventionally. The highest improvement was found in highly motivated students in the experimental group (58.89 points), followed by low-motivation students in the experimental group (40.33 points). Meanwhile, the conventional groups showed improvements of 52.00 points and 35.71 points, respectively. The average posttest score of the experimental class (76.80) was higher than that of the control class (68.67). Statistical analysis revealed that instructional media significantly affected students’ chemistry conceptual understanding (F = 11.091; p < 0.05), and learning motivation also showed a significant effect (F = 112.853; p < 0.05). However, no significant interaction was found between instructional media and learning motivation (F = 0.216; p > 0.05). These findings indicate that PhET Chemistry Simulations effectively improve students’ conceptual understanding across different motivational levels.